Compressive mechanical properties of Zr-based bulk metallic glass composites reinforced with entangled porous tungsten wire - Sen Chen; Hangtian Zhu; Jinhe Wang; Huan Huang; Jiawang Zhang; Yong Wang; Huan Wang; Guohua Sun; Lishi Jiao; Wei Li; Zhengkun Li; Zhengwang Zhu; et al. (Journal of Materials Research and Technology)
Tungsten wire reinforced bulk metallic glass composites can be used as penetrator due to their excellent self-sharpening ability. The direction or distribution of tungsten wire plays a great role in deformation and fracture behaviors of the bulk metallic glass composites. In this study, a new kind of bulk metallic glass composites reinforced with entangled porous tungsten wires were designed, aiming to investigate the effect of entangled porous tungsten wire on the deformation and fracture behaviors of the composites. As increasing the volume fraction of tungsten wire, the yield stress increases and reaches to a stable value, while the ultimate stress increases firstly and then slightly decreases. The composites with lower volume fraction of tungsten wire exhibit brittle fracture, whereas, the composites with larger volume fraction of tungsten wire show plastic strain of more than 5%. Furthermore, the effect of entangled porous tungsten wire on the shear band formation and propagation was analyzed and discussed. All of these composites fractured in a shear mode, which is beneficial for the self-sharpening ability. These new bulk metallic glass composites can broaden the application of tungsten wire reinforced bulk metallic glass composites.